Estudio preliminar sobre Fasciola hepatica en Costa Rica - Brenes, Rodrigo Ramón (1967)
The literature on Fasciola hepatica in Costa Rica is briefly reviewed. The first report of an intermediate host in this country is made: Lymnaea (PIeudosuccinaea) columella Say, found showing heavy natural infestation in Grano de Oro, Moravia de Chirripó, Cartago. Part of the life cycle was experimentatIy observed, infecting rabbits oratIy with melacercariae and finding adult trematodes in their bite ducts three months later. Human inhabitants of the same district were tested with total F. hepatica antigen; out of 82 tests, 47(57%) gave positive reactions.